1990
DOI: 10.1111/j.1834-7819.1990.tb03023.x
|View full text |Cite
|
Sign up to set email alerts
|

After‐hours treatment of anterior dental trauma in Newcastle and western Sydney: a four‐year study

Abstract: This study investigated anterior dental trauma presenting after-hours in Newcastle and western Sydney. During the four-year period 1983-1986, all patients presenting with anterior dental injuries to the Royal Newcastle Hospital (n = 382) or Westmead Hospital (n = 362) on week nights, weekends or public holidays were studied. In both areas, upper central incisors were the teeth injured most frequently. The mean numbers of teeth injured per patient were 1.9 at Newcastle and 2.0 at Westmead. The frequencies of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 5 publications
11
54
1
Order By: Relevance
“…The findings of this survey revealed that fall was the most frequent etiologic factor, corresponding to almost forty-one percent of all cases of dentoalveolar trauma, which agrees with the outcomes of previous studies 8,15,[20][21][22][23] . Few cases of dentoalveolar traumatic injuries were attributed to sports accidents (3.4%), which is consistent with the results of other authors 20,24 .…”
Section: Discussionsupporting
confidence: 80%
“…The findings of this survey revealed that fall was the most frequent etiologic factor, corresponding to almost forty-one percent of all cases of dentoalveolar trauma, which agrees with the outcomes of previous studies 8,15,[20][21][22][23] . Few cases of dentoalveolar traumatic injuries were attributed to sports accidents (3.4%), which is consistent with the results of other authors 20,24 .…”
Section: Discussionsupporting
confidence: 80%
“…Injuries to all teeth were recorded in this study compared with other studies where only injuries to either anterior teeth, or specifically, injuries to primary or permanent teeth were recorded. This high number of injuries per patient has also been reported by Martin et al 3 and Galea 13 where data were collected from casualty and emergency departments at hospitals. This may once again suggest that patients experiencing more severe injuries, or injuries occurring after hours, attend hospitals rather than public or private dental clinics.…”
Section: Discussionsupporting
confidence: 74%
“…The highest frequency of trauma occurred in the 6-10 year old age group and was in agreement with other studies. 3,5,6,11 Playing and riding bicycles were the most frequently associated activities, while in the 16-20 year old group fighting and sport were the predominant activities. Assaults or fights were also the second and third most common cause of dental injury in studies by Davis and Knott 5 and Perez et al 12 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations